Efficient Transient Expression of Recombinant Proteins Using DNA Viral Vectors in Freshwater Microalgal Species - Malla, Ashwini; Rosales-Mendoza, Sergio; Phoolcharoen, Waranyoo; Vimolmangkang, Sornkanok (Frontiers in Plant Science, 2021)
The increase in the world population, the advent of new infections and health issues and the scarcity of natural biological products have spotlighted the importance of recombinant protein technology and its large-scale production in a cost-effective manner. Microalgae has become a significant promising platform with the potential to meet the increasing demand for recombinant proteins and other biologicals. Microalgae are safe organisms that can grow rapidly and are easily cultivated with basic nutrient requirements. Although continuous efforts have led to considerable progress in the algae genetic engineering field, there are still many hurdles to overcome before these microorganisms emerge as a mature expression system. Hence, there is a need to develop efficient expression approaches to exploit microalgae for the production of recombinant proteins at convenient yields. This study aimed to test the ability of the DNA geminiviral vector with Rep-mediated replication to transiently express recombinant proteins in the freshwater microalgal species C. reinhardtii and C. vulgaris using Agrobacterium-mediated transformation. The SARS-CoV-2 RBD and bFGF are representative antigen proteins and growth factor proteins, respectively, that were subcloned in a geminiviral vector and were used for nuclear transformation to transiently express these proteins in C. reinhardtii and C. vulgaris. The results showed that the geminiviral vector allowed the expression of both recombinant proteins in both algal species, with yields at 48 hours posttransformation of up to 1.14 µg/g RBD and 1.61 ng/g FGF in C. vulgaris and 1.61 µg/g RBD and 1.025 ng/g FGF in C. reinhardtii. Thus, this study provides a proof of concept for the use of DNA viral vectors for the simple, rapid, and efficient production of recombinant proteins that repress the difficulties faced in the genetic transformation of these unicellular green microalgae. This concept opens an avenue to explore and optimize green microalgae as an ideal economically valuable platform for the production of therapeutic and industrially relevant recombinant proteins in shorter time periods with significant yields.